Pesan Dakwah dalam Q.S. Ar-Ra’d [13]: 11 Ditinjau dari Penafsiran Klasik-Kontemporer - Rahman, Muhammad Iqbal; Erdiyansyah, Erdiyansyah (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2024)
Q.S. Ar-Ra'd [13]: 11 is a verse familiar to Muslims, including Muslims in Indonesia. This is reflected in the many texts that quote, explain, and translate Q.S. Ar-Ra'd [13]: 11 on various platforms, both online and offline media. However, some motivators only convey snippets of the verse without knowing the real meaning of the verse. This impacts the public's understanding as an audience who considers Q.S. Ar-Ra'd [13]: 11 to be a motivational verse, differing in opinion from commentators in general. Therefore, this article raises the main issue, "What is the meaning of the verses and message of da'wah in Q.S. Ar-Ra'd [13]: 11 in terms of classical, middle, and modern-contemporary interpretations?" The method used in this paper is descriptive analysis. The approach used in this paper is historical-sociological. The results of this paper find that the meaning of Q.S. Ar-Ra'd [13]: 11 is the existence of hafazhah angels who continuously protect and protect humans from evil and disgraceful behavior. These angels also encourage humans to do good deeds, so a Muslim will try to continue improving his life for this world and the hereafter. Then, the message of da'wah in Q.S. Ar-Ra'd [13]: 11 includes (1) perfect knowledge possessed by Allah SWT. as the Lord of the Universe – all the movements of His creatures are monitored by media in the form of His messenger angels who stand guard day and night within humans; (2) The pleasure that exists within a person will not change unless there are changes that result in the pleasure being reduced, or even gone; (3) Nothing can hinder God's will.